Identifikasi faktor penyebab kejadian unsafe action dan unsafe condition pada pekerja lapangan - Syalfi Intan Riyani; Budi Aswin; Herwansyah Herwansyah; Usi Lanita (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Workplace accidents remain a major concern in the energy sector. Unsafe acts and conditions are the leading cause of accidents, with over 85% of incidents related to unsafe behavior. PT. PLN Indonesia Power's Payo Selincah Jambi Power Plant Unit, with 144 workers, recorded 99 workplace accidents in 2019–2021.Purpose: To identify factors underlying unsafe acts and unsafe conditions among field workers.Method: Qualitative research using a case study approach. Six informants were purposively selected: the unit manager, the OHS team leader, the head of operations, the head of maintenance, and two field workers. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically.Results: Two main themes were identified: human behavioral factors, low PPE compliance due to unfamiliarity and discomfort,